TMJ energy densities in healthy men and women - Iwasaki, L.R.; Gonzalez, Y.M.; Liu, Y.; Liu, H.; Markova, M.; Gallo, L.M.; Nickel, J.C. (Osteoarthritis and cartilage, 2017)
Cartilage fatigue, due to mechanical work, may account for the early development of degenerative joint disease (DJD) in the temporomandibular joint (TMJ), and why women are three times more likely to be afflicted. This study tested for gender differences in mechanical energy densities in women and men with healthy TMJs. Eighteen women and eighteen men gave informed consent. Research diagnostic criteria including imaging were used to ensure that subjects' TMJs were normal, without disc displacement or signs of DJD. Numerical modeling determined TMJ loads (Fnormal). Jaw tracking and three-dimensional dynamic stereometry characterized individual-specific data of stress-field dynamic mechanics during 10 symmetrical jaw closing cycles. These data were used to estimate tractional forces (Ftraction). Energy densities were then calculated, where: Energy Density = W/Q (W = work done or mechanical energy input = Ftraction*distance of stress-field translation, Q = volume of cartilage). Two-way analysis of variance (ANOVA) and follow-up two-group comparisons tested mean energy densities for ipsilateral and contralateral TMJs in women vs men. Mean energy densities ± standard deviations in ipsilateral and contralateral TMJs in women were 9.0 ± 9.7 and 8.4 ± 5.5 mJ/mm3, respectively, and were significantly larger (P = 0.004 and 0.001, respectively) compared to ipsilateral and contralateral TMJs in men, which were 5.6 ± 4.2 and 6.3 ± 4.2 mJ/mm3, respectively. Energy densities were significantly larger in healthy TMJs of women than men. Larger TMJ energy densities during normal jaw functions could predispose earlier mechanical fatigue of the TMJ disc.